Effectiveness of Microbial (Entomopathogenic) agents and Botanical extracts against small rice grasshoppers (Oxya hyla hyla) - et al., Manika Das (International Journal of Advanced Science and Technology, 2019)
The use of agro- chemicals and bio- pesticides are the most important and effective tool available to the rice farmer to eradicate the pest problem. Excessive dependence on synthetic chemicals has created various problems including pest resistance and environmental pollution leading to health hazards. Hence, it was necessary to evaluate the insecticidal properties of biological products which are comparatively safe, effective and easily available. In this study,five microbial organisms and four botanical extracts were evaluated against O. hyla hyla in the crop field. Among the microbial agents, maximum (95.83%) mortality was recorded by Penicillium citrinum with both the concentrations (0.4 and 0.8%) and Trichoderma viride with higher concentration (1.0%) after a week. As the period of treatment increases the performance of these agents effectiveness were also increased and vice- versa. Among the botanical extracts, E. odoratum proved better performance over other plant leaf extracts as their residual life persists up to a week. Among the two solvents (Methanol, Petro- benzene), methanol proved to be the best against the O. hyla hyla pest species. ANOVA indicated significant different performances among all the treatments in both the biological products.